Pelatihan Pembuatan Kuliner Ikan Wadi Patin Bagi Mahasiswa Program Studi Pendidikan Ekonomi Upr Dalam Menumbuhkan Minat Wirausaha - Lenlioni, Liling; Buji, Grace Evelina; Sundari, Sundari; Hariatama, Fendy; Febiola, Fransiska Jeni (Jurusan Pendidikan Ilmu Pengetahuan Sosial, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
The training activity on making Wadi fish culinary for students of the Economics Education Study Program at UPR aims to equip students with skills and entrepreneurial insights. One form of entrepreneurial learning that can be applied is through the introduction of regional culinary specialties as business opportunities. The socialization of Wadi fish making, a traditional culinary dish of the Dayak ethnic group, has become one of the efforts to increase the entrepreneurial interest of students from the Economics Education Study Program at the University of Palangka Raya (UPR). The method used in this community service is participatory, with an approach focused on enhancing the active role of students in the training process. The training techniques are varied, including lectures, Q&A sessions, and demonstrations. Data collection techniques were carried out through observation, interviews, and documentation. The results of the training indicate an increase in students' interest in entrepreneurship, particularly in the culinary sector based on local wisdom, which can help create self-employment opportunities and provide a positive impact on the surrounding community